Design of bicycling suitability maps for hilly cities - Tralhao, Lino (2016)
Sustainability worries related to the intensive use of energy by automobiles and traffic congestion issues have encouraged decision makers to look for alternative solutions, leading to an emerging shift towards soft/active transport modes. The bicycle, a very efficient mode of transport, is a soft travel mode that can be adopted in most cities, contributing to urban sustainability given the associated environmental, economic and social advantages. Cycling, however, also has its deterrents. Among these, it is recognised that slopes play an important role in influencing the choice for this mode of travel. The purpose of this paper is to present methods to analyse a hilly city’s suitability for cycling, in what concerns relief, with the aim of identifying locations for implementation of hard aid devices that restore connectivity between most parts, or even the whole, of the city. The methodology proposed makes use of appropriate service areas. Geographical information systems technology was used to implement the methodology and the approach is demonstrated with a case study for the city of Coimbra, Portugal. This combined approach helps decision makers to plan the city in a sustainable way.